Evidence-based mentoring in higher education - Peterson, L.; Dixon, Kathryn (Common Ground Publishing, 2014)
This paper develops the High Impact Mentoring Model (HIMM) as a conceptual and practical mechanism for supporting academic teaching practices within higher education. The HIMM was developed as a result of an action research study which was undertaken in the New Zealand higher education context and reflects a synthesis of the research findings. Using the analogy of mentoring as a progressive, iterative process, the HIMM suggests a process oriented approach to implementing an organisation-wide mentoring process with embedded systemic evaluation strategies to determine the outcomes of mentoring. A number of key components represent the multi-dimensional nature of the HIMM, such as the mentor selection process, the process for matching mentees with mentors, the provision of mentoring training, and the establishment of communities of practice for mentors and mentees as an additional support mechanism within a mentoring programme. The HIMM builds on a conceptual framework which positions mentoring as a pivotal link for connecting the individual teacher within the larger sphere of the organisation and is of key importance to stakeholders within higher education contexts including but not limited to teachers, professional development providers, managers, and the organization as a strategic whole. It is a model for mentoring that is not only applicable for higher education, but has broader applications in other contexts such as health and business. The HIMM seeks to guide the process for including teacher mentoring as one of the organisation’s support mechanisms to facilitate teacher professional development that is theoretically, contextually, and strategically framed.